Sodium butyrate alleviates free fatty acid-induced steatosis in primary chicken hepatocytes via the AMPK/PPARα pathway - Jiayi Ding; Jiuyue Liu; Jinyan Chen; Xinyi Cheng; Huabin Cao; Xiaoquan Guo; Guoliang Hu; Yu Zhuang (Poultry Science, 2024)
ABSTRACT: Fatty liver hemorrhagic syndrome (FLHS) is a prevalent metabolic disorder observed in egg-laying hens, characterized by fatty deposits and cellular steatosis in the liver. Our preliminary investigations have revealed a marked decrease in the concentration of butyric acid in the FLHS strain of laying hens. It has been established that sodium butyrate (NaB) protects against metabolic disorders. However, the underlying mechanism by which butyrate modulates hepato-lipid metabolism to a great extent remains unexplored. In this study, we constructed an isolated in vitro model of chicken primary hepatocytes to induce hepatic steatosis by free fatty acids (FFA). Our results demonstrate that treatment with NaB effectively mitigated FFA-induced hepatic steatosis in chicken hepatocytes by inhibiting lipid accumulation, downregulating the mRNA expression of lipo-synthesis-related genes (sterol regulatory element binding transcription factor 1 (SREBF1), acetyl-CoA carboxylase 1(ACC1), fatty acid synthase (FASN), stearoyl-CoA desaturase 1 (SCD1), liver X receptor α (LXRα), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR)) (P < 0.05), and upregulating the mRNA and protein expression of AMP-activated protein kinase α1 (AMPKα1), peroxisome proliferator-activated receptor α (PPARα), and carnitine palmitoyl-transferase 1A (CPT1A) (P < 0.05). Moreover, AMPK and PPARα inhibitors (Compound C (Comp C) and GW6471, respectively) reversed the protective effects of NaB against FFA-induced hepatic steatosis by blocking the AMPK/PPARα pathway, leading to lipid droplet accumulation and triglyceride (TG) contents in chicken primary hepatocytes. With these findings, NaB can alleviate hepatocyte lipoatrophy injury by activating the AMPK/PPARα pathway, promoting fatty acid oxidation, and reducing lipid synthesis in chicken hepatocytes, potentially being able to provide new ideas for the treatment of FLHS.